Effect of Muscle Energy Technique versus Graston Technique on non-specific neck pain - Elsayed, Mohamed; Ahmed Mohamed, Mohamed; Ali, Mohammad F.; Dabash, Ghada R.; El Din Taha, Taher Salah; Abdelrahim, Reham M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Background: Numerous researches have been carried out in order to determine the most effective physical therapy strategy for treating nonspecific neck pain (NSNP). Purpose: To contrast between the outcomes of Graston Technique (GT) and Muscle Energy Technique (MET) on both pain intensity and functional disability in patients with NSNP. Methods: Forty-two (30 males and 12 females) patients with NSNP divided randomly into three groups: Group A: received Graston Technique and traditional physiotherapy treatment (TPT), Group B: received muscle energy technique and TPT, and Group C: received TPT only. Intervention lasted for 12 sessions (3 per week). At the start and finish of the fourth week, a visual analogue scale was used to quantify pain intensity and a neck disability index (NDI) questionnaire was used to measure functional disability. Results: There were significant mean effects of time (pre/post) and intervention group (Graston, MET, conventional) and significant interaction on pain and disability (p<0.05). MET group had higher changes in the pain than both Graston and control groups (p<0.05). However, no significant differences among groups in the functional change. Conclusion: GT and MET had similar effects on the function in patients with NSNP, but MET had higher effects on reducing pain.